Experimental study of paddy drying in a vortex chamber. Issue 9 (3rd July 2016) - Pati, Jnyana Ranjan; Dutta, Subhajit; Eliaers, Philippe; Mahanta, Pinakeswar; Chatterjee, Pradip Kumar; De Wilde, Juray
ABSTRACT: The intensification of interfacial mass, heat, and momentum transfer makes vortex chambers potentially interesting for the efficient drying of paddy, allowing shorter drying times and/or more compact equipment. The presence of a shell introduces particular challenges. Intraparticle diffusion limitations are strong and may reduce the advantage from intensified interfacial mass and heat transfer and the efficiency of air usage. Furthermore, high shear and normal stresses in the fast rotating particle bed may cause damage to the paddy shell, posing problems for transport and storage. With these specific aspects in mind, the use of vortex chambers for paddy drying is experimentally evaluated.